1991
DOI: 10.1111/j.1540-8191.1991.tb00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity, Antigenicity, and Endothelial Viability of Aortic Valves Preserved at 4°C in a Nutrient Medium

Abstract: In patients undergoing aortic valve replacement, allograft valves stored at 4 degrees C in a nutrient medium have been associated with excellent immediate and long-term results. The effects of this method of prolonged storage on the antigenic, immunological and cellular characteristics of these grafts are incompletely understood. This study was designed to study these phenomena in rat aortic valves subjected to antibiotic sterilization and stored for up to 3 weeks in RPMI containing 10% fetal calf serum. Selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…However, cryopreserved homografts develop a slow but defi nite allogeneic immunologic reaction leading to SHVD, particularly when implanted in young patients. 12,13 In addition, recent advances in biologic valves may make them more acceptable than homograft valves. 14,15 Despite their negative features, homografts still have a strong appeal to surgeons because of their excellent handling characteristics during fragile tissue reconstruction, particularly in active endocarditis [16][17][18][19] and at the time of the Ross operation.…”
Section: Discussionmentioning
confidence: 99%
“…However, cryopreserved homografts develop a slow but defi nite allogeneic immunologic reaction leading to SHVD, particularly when implanted in young patients. 12,13 In addition, recent advances in biologic valves may make them more acceptable than homograft valves. 14,15 Despite their negative features, homografts still have a strong appeal to surgeons because of their excellent handling characteristics during fragile tissue reconstruction, particularly in active endocarditis [16][17][18][19] and at the time of the Ross operation.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 All of these factors could have an impact on the durability of the allograft after implantation. Some centers continue to advocate the use of fresh valves maintained at 4°C and implanted within hours to a few days.…”
mentioning
confidence: 99%
“…These degenerative changes have been largely confirmed in a number of experimental models of large-vessel transplantation that have emerged over the years [lo]. The general theme behind the investigations that followed the application of these models focused on the effects of cold preservation on the immunogenicity and endothelial cell viability of such grafts [7,10,17,181. These studies suggested that these grafts were especially prone to rejection because their recipients did not receive immunosuppression.…”
Section: Discussionmentioning
confidence: 99%